FGF21 induces autophagy‐mediated cholesterol efflux to inhibit atherogenesis via RACK1 up‐regulation. Issue 9 (30th March 2020) - Xiaolong, Lin; Dongmin, Guo; Liu, Mihua; Zuo, Wang; Huijun, Hu; Qiufen, Tan; XueMei, Hu; Wensheng, Lin; Yuping, Pan; Jun, Lin; Zhaolin, Zeng
Abstract: Fibroblast growth factor 21 (FGF21) acts as an anti‐atherosclerotic agent. However, the specific mechanisms governing this regulatory activity are unclear. Autophagy is a highly conserved cell stress response which regulates atherosclerosis (AS) by reducing lipid droplet degradation in foam cells. We sought to assess whether FGF21 could inhibit AS by regulating cholesterol metabolism in foam cells via autophagy and to elucidate the underlying molecular mechanisms. In this study, ApoE −/− mice were fed a high‐fat diet (HFD) with or without FGF21 and FGF21 + 3‐Methyladenine (3MA) for 12 weeks. Our results showed that FGF21 inhibited AS in HFD‐fed ApoE −/− mice, which was reversed by 3MA treatment. Moreover, FGF21 increased plaque RACK1 and autophagy‐related protein (LC3 and beclin‐1) expression in ApoE −/− mice, thus preventing AS. However, these proteins were inhibited by LV‐RACK1 shRNA injection. Foam cell development is a crucial determinant of AS, and cholesterol efflux from foam cells represents an important defensive measure of AS. In this study, foam cells were treated with FGF21 for 24 hours after a pre‐treatment with 3MA, ATG5 siRNA or RACK1 siRNA. Our results indicated that FGF21‐induced autophagy promoted cholesterol efflux to reduce cholesterol accumulation in foam cells by up‐regulating RACK1 expression. Interestingly, immunoprecipitation results showed that RACK1 was able to activate AMPK and interact with ATG5. Taken together, our results indicated that FGF21 induces autophagy to promote cholesterol efflux and reduce cholesterol accumulation in foam cells through RACK1‐mediated AMPK activation and ATG5 interaction. These results provided new insights into the molecular mechanisms of FGF21 in the treatment of AS.